Islamic Junior High School Teachers’ Perceptions, Practices And Problems in Conducting Classroom Action Research - Sri Wahyuni (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This article aims at investigating teachers’ perception, practices and problems in conducting classroom action research (CAR). This study employed a descriptive quantitative research design using a survey. Forty-five teachers from two different State Islamic Junior High Schools in Kediri are randomly selected. To collect the data, an open-ended questionnaire is used as the instruments. To analyze the data, descriptive statistics analysis is used. The finding shows that the teachers have a good perception of CAR. Almost of them agreed that it could improve the quality of their teaching and learning process, improve students’ motivation and achievement and improve their professional rank. Their good perception of CAR can be seen from their practice in conducting CAR. Majority of them have experience in conducting CAR; however, some of them still get difficulty in making the report. The teachers also face some problems in conducting CAR. Those are time, reporting system, in-existence of the supervisor, lack of understanding of research, insufficient references, research budget, and incomplete facilities. The alternative solution is by conducting the research collaboratively with their colleagues in the same subject. It is recommended for the school stakeholder to consider this finding in making the school policy, especially in increasing teacher professionalism.